Spatial distribution management of Crustacea (Decapoda) based on conservation in tropical tidal lake (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Muhtadi A, Yulianda F, Boer MF, Krisanti M. 2022. Spatial distribution management of Crustacea (Decapoda) based on conservation in tropical tidal lake. Biodiversitas 23: 4064-4072. Siombak Lake has a unique biological system impacted by high and low tides. Crustaceans (Decapoda) found in this lake are predicted to establish distinctive communities due to their interaction with two biological systems of seawater and freshwater. Therefore, this study aimed to determine the characteristics and distribution of crustacean communities in Siombak Lake, which were influenced by high and low tides. Crustacean samples were taken and observed every month at high and low tides with traps from September 2018 to August 2019. The crustaceans discovered included 5 families and 18 species, with 13 crabs and 5 shrimp. The communities' distribution is extremely dynamic, as seen by the emergence of mangrove crabs at high tide and fiddle crabs during low tide. The crustacean communities are more influenced by tidal ecology, characterized by a higher abundance of individuals at high tide. Furthermore, crustacean density fluctuates throughout the year and reaches the highest in March with 8679 ind/100m2. Penaeid shrimp are always found at high and low tides, dominated by Parapenaeopsis coromandelica, while mangrove crabs are only found at high tide. Therefore, efforts are required to conserve mangrove crabs and enhance their habitats for sustainable usage.
Keywords: Biodiversity, coastal lake, crab, prawn, shrimp